Pertumbuhan dan Dimensi Tubuh Anak Kambing sebagai Respons Pemberian PMSG pada Induk sebelum Dikawinkan - Adriani, Adriani (Fakultas Peternakan Universitas Jambi, 2011)
Fifty Four birth goat were used to study the growth and body dimensions by response of giving PMSG at prior to mating. The experimental does were injected with pregnant mare serum gonadothrophin (PMSG), 0 IU/kg BW and 15 IU/kg BW. Intravaginal sponge (60 mg medroxyprogesterone acetate) was applied for 14 days to synchronize estrus cycle. Twenty four hours prior to sponge removal, PMSG was injected to stimulate PMSG, than, 5 does were mixed with 1 buck for natural mating. The results showed that administration of PMSG at prior to mating of the does can increase of the birth weight (p<0.01), weaning weight, body weight. Giving PMSG also increased body length at birth, body length at weaning and raising of body length (p<0.01). Giving PMSG increased shoulder height at birth, high shoulders weaned and raising of high shoulder weaning kid. Giving PMSG of the parent can increase the chest circumference at birth, chest circumference at weaning, and chest circumference of the offsprings (p<0.05). The experiment results indicated that PMSG at prior to mating increased birth weight and body dimensions, weight gain until weaning off significantly higher than goats without giving PMSG.